FORMS OF VIOLENCE AGAINST WOMEN (E Conference Zone, 2022)
Violence is committed by someone the woman knows, not a stranger. The study provides convincing evidence that violence against women is a serious and widespread problem around the world and has a devastating impact on the health and wellbeing of women and children